Uji Kandungan Gas Sulfur Dioksida (SO2) pada Udara Ambien Akibat Adanya Pembakaran Batubara PLTU Nii Tanasa, Sulawesi Tenggara - Halulanga, Alifya Julya; Rosdiana, Rosdiana; Adami, Aryani (Universitas Muhammadiyah Kendari, 2021)
Along with the high demand for electrical energy consumption by the Indonesian people, it will also affect the increase in the construction of power plants in various regions. PLTU Nii Tanasa is one of the power plants located in the Lalonggasumeeto District, Konawe Regency, Southeast Sulawesi. This PLTU uses coal as the main raw material in producing electrical energy. This study analyzed the SO2 content in the exhaust gas of PLTU Nii Tanasa. Based on the results of the study, the concentration of SO2 gas in Nii Tanasa Village was 99.31 g/Nm3. The temperature conditions at the time of sampling were 30ºC and the wind speed was 3.7 km/hour. Meanwhile, point 2 is located in Rapambinopaka Village, the distance from the pollutant source is ± 1 km, the concentration of SO2 gas is 147.69 g/Nm3. The temperature at the time of sampling was 25ºC and the wind speed was 3.7 km/hour. The increase in upper respiratory infection disease that occurs every year is not caused by air pollution, especially SO2 parameters.